Galoisian and numerical approach of three dimensional linear differential systems with skew symmetric matrices defined in a non- constant differential field (2018)
This work contrasts numerical methods with algebraic methods. These methods are applied to solve a three dimensional linear differential system with skew symmetric matrices defined in a non- constant differential field. Algorithms and methods of Differential Galois Theory, are used to provide an algebraic solution, while numerical methods, in particular, methods from Runge - Kutta family, are applied to the same system. Finally, the absolute and relative errors between Liouvillians solution are calculated comparing the solutions obtained by means of algebraic methods and by means of numerical methods.